Phrasal Movement in the Bantu Verbal Complex: Deriving Affix Scope and Order in Kîîtharaka. (2nd August 2013) - Muriungi, Peter Kinyua
Abstract This paper investigates multiple suffixation in Kîîtharaka, an SVO Bantu language spoken in Kenya (code E54 in the Guthrie classification). Assuming as a starting point that semantic scopes are encoded in syntax such that if an affix A scopes over an affix B, A asymmetrically c‐commands B, this paper argues that linearization from the base semantic scope to the phonological form is easily derived by phrasal movement. The novelty in the paper is the presentation and discussion of semantic scopes between suffixes and the overt assumption that scopes are encoded in the syntax. Furthermore, this paper breaks from the Bantu tradition of examining the scopes between argument‐related suffixes such as the causative, applicative, reciprocal and passive, and goes further to include aspectual morphemes such as the perfective and the habitual and adverbial‐like suffixes such as the erratic. This paper shows that the verbal complex containing argument‐related, aspectual, and adverbial‐like suffixes arises from the syntactic hierarchy determined by scope via restricted phrasal movement.